PENGARUH BEBAN KERJA DAN WORK FAMILY CONFLICT MELALUI WORK LIFE BALANCE SEBAGAI VARIABEL INTERVENING TERHADAP TURNOVER INTENTION KARYAWAN SHOPEE DI JAKARTA - Fadilla Azahra Suhendar (2023)
The workload phenomenon on shopee felt by employees is quite heavy and targets continue to increase, especially during twin dates. The perceived physical and non-physical workload of employees can increase the turnover rate of intention. But not only workload, work-family conflict that occurs in employee life is also one of the factors causing turnover intention. Things that often happen in growing startup companies, employees are required to work longer than normal working hours. This affects the work-life balance of employees, so they cannot balance their work life with their personal life. This research is a quantitative study with the population of Shopee employees in Jakarta who have criteria for staff/non-manager positions, amounting to 550 employees. The sample amounted to 85 respondents taken using purposive sampling techniques and convenience sampling techniques. The results stated that the workload variable positively affected turnover intention. Then the work family conflict variable positively affects turnover intention. The variable turnover intention also positively affects work-life balance. It can be concluded that workload variables, work-family conflict, and work-life balance have a positive and significant effect on the turnover intention of Shopee employees in Jakarta.